(untitled) (Terr@ Plural, 2021)
The state of Tocantins has been the subject of several paleontological types of research in the past; however, the Devonian fossils have recently been poorly investigated. This paper expands the knowledge about Devonian in the state of Tocantins, presenting a bibliographic review and adding new fossiliferous discoveries. During fieldwork, brachiopods (Australocoelia, Australospirifer, Derbyina, infaunal lingulids, Orbiculoidea, Tropidoleptus carinatus, Schuchertella), cnidarians (Conularia quichua), crinoids (Exaesiodiscus dimerocrinosus, Laudonomphalus, Monstrocrinus), mollusks (Platyceras, Nuculites, Palaeoneilo, Sanguinolites), and plants remains (Spongiophyton lenticularis) were found in different sedimentary facies of the Pimenteira Formation.